MicroRNA filters Hox temporal transcription noise to confer boundary formation in the spinal cord - Chung-Jung Li (Nature Portfolio, 2017)
In the spinal cord, someHox genes are transcribed in progenitors while their proteins are only detected in differentiating postmitotic motor neurons. Here, the authors show that miRNAs (specifically mir-27) regulate post-transcriptional Hoxa5 expression in motor neurons.